The relationship between PBI values in periodontitis patients based on gender: Study observational - Aprilita, Aweni Tria; Komala, Olivia Nauli (Padjadjaran Journal of Dental Researchers and Students, 2024)
ABSTRACTIntroduction: Periodontitis is an inflammatory disease of the supporting teeth tissues. According to Riset Kesehatan Dasar (Riskesdas) in 2018, the prevalence of periodontitis in Indonesia reached 74.1%. Clinical signs of periodontitis include gingival inflammation, margin swelling, loss of attachment, periodontal pocket formation, and gingival bleeding on probing. The Papillary Bleeding Index (PBI) is a periodontal index used to measure the severity of gingival inflammation. The PBI value can be influenced by several factors, one of which is gender. Hormonal fluctuations in the body, especially in women, can be seen in the mouth. The aim of the study was to analyse the difference between PBI values in periodontitis patients based on gender. Methods: Analytical observational research with a cross-sectional research design. The sample is periodontal status examination sheets of patients treated at RSGM-P FKG Usakti for the period 2019 - 2022. Data analysis uses the Mann-Whitney statistical test. Results: The majority of periodontitis sufferers at RSGM-P FKG Usakti in 2019 -2022 had a PBI score in the range of 1 - 1.99 in both female and male genders. The results of the Mann-Whitney test showed that there was no significant difference (p = 0.12) between the female and male groups regarding the PBI value. Conclusion: There is no difference between PBI values and gender in periodontitis patients.KEY WORDS: Periodontitis, papillary bleeding index, gingival inflammation, genderPerbedaan nilai papillary bleeding index pada pasien periodontitis berdasarkan jenis kelamin: studi cross sectionalABSTRAKPendahuluan: Periodontitis adalah penyakit inflamasi pada jaringan pendukung gigi. Menurut data Riset Kesehatan Dasar (Riskesdas) tahun 2018 prevalensi periodontitis di Indonesia mencapai 74,1%. Tanda klinis periodontitis berupa inflamasi gingiva, pembengkakan margin, kehilangan perlekatan, pembentukan poket periodontal, dan perdarahan gingiva saat probing. Papillary Bleeding Index (PBI) merupakan indeks periodontal yang digunakan untuk mengukur tingkat keparahan inflamasi gingiva. Nilai PBI dapat dipengaruhi oleh beberapa faktor, salah satunya jenis kelamin. Fluktuasi hormon pada tubuh terutama pada perempuan, dapat mempengaruhi perubahan di dalam rongga mulut. Tujuan penelitian menganalisis perbedaan nilai PBI pada pasien periodontitis berdasarkan  jenis kelamin. Metode: Penelitian observasional analitik dengan rancangan penelitian cross sectional. Sampel berupa lembar pemeriksaan status periodontal pasien yang dirawat di RSGM-P FKG Usakti periode 2019 - 2022. Analisis data menggunakan uji statistik Mann-Whitney. Hasil: Penderita periodontitis di RSGM-P FKG Usakti tahun 2019 - 2022 mayoritas memiliki skor PBI dengan rentang 1- 1,99, baik pada jenis kelamin perempuan maupun laki-laki. Hasil uji Mann-Whitney menunjukkan tidak terdapat perbedaan bermakna (p=0,12) antara kelompok perempuan dengan laki-laki terhadap nilai PBI. Simpulan: Tidak terdapat perbedaan antara nilai PBI dengan jenis kelamin pada pasien periodontitis.KATA KUNCI: Periodontitis, papillary bleeding index, inflamasi gingiva, jenis kelamin